Plasmon‐Dictated Photo‐Electrochemical Water Splitting for Solar‐to‐Chemical Energy Conversion: Current Status and Future Perspectives - Xiao, Fang‐Xing; Liu, Bin (Advanced materials interfaces, 2018)
Surface plasmon resonance (SPR) effect of metal nanostructures is established as an efficient and attractive strategy to boost visible‐light or even near‐infrared‐responsive photo‐electrochemical (PEC) water splitting devices for substantial solar‐to‐chemical energy conversion. Rational integration of plasmonic metal nanostructures with semiconductors in an appropriate fashion is beneficial for creating a large variety of plasmonic metal/semiconductor photoelectrodes. However, up to date, construction of well‐defined and highly efficient plasmonic metal/semiconductor heterostructures is still in its infant stage. In this review, basic principles of PEC water splitting over semiconductors, SPR‐excited plasmonic effect of metal nanostructures, and their intrinsic correlation with each other are first concisely introduced. Subsequently, it is paid great attention to specifically summarize the diverse plasmonic metal/semiconductor photoelectrodes currently being extensively explored for indirect plasmon‐induced PEC water splitting. Particularly, different plasmonic metal/semiconductor nanoarchitectures including planar thin films, 1D composited, and 3D spatially hierarchical heterostructures are systematically classified and elucidated. Finally, future perspectives and challenges in triggering further innovative thinking on plasmon‐enhanced solar water splitting are envisaged. It is anticipated that this review can provide enriched information on rational design and construction of various plasmonic metal/semiconductor heterostructures for solar‐powered plasmon‐based PEC devices. Surface plasmon resonance effect of metal nanostructures is established as an efficient and attractive strategy to boost visible‐light or even near‐infrared‐responsive photo‐electrochemical water splitting devices for substantial solar‐to‐chemical energy conversion. In this review article, different plasmonic metal/semiconductor nanoarchitectures including planar thin films, 1D composited, and 3D spatially hierarchical heterostructures are comprehensively and systematically elucidated.